2016
DOI: 10.1016/j.pmrj.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐Associated Collapse: Is Hyponatremia in Our Head?

Abstract: Exercise-associated hyponatremia (EAH) is one of the most common causes of exercise-associated collapse. The primary pathogenesis of EAH is largely the result of excessive fluid intake but is influenced by other factors, including hormonal abnormalities (ie, inappropriate arginine vasopressin secretion), renal abnormalities, and mobilization of sodium stores. Early recognition of EAH is crucial to appropriate treatment, because symptoms are varied and may be confused with other causes of exercise-associated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…It is defined by a serum, plasma, or blood sodium concentration below the reference laboratory range, which for most laboratories is <135 mmol/L [44]. Exercise-associated hyponatremia is serious and one of the potential causes of exercise-associated collapse [45] which can be fatal [42]. While sometimes asymptomatic, EAH can result in a myriad of signs and symptoms mimicking other conditions, including confusion, dyspnea, nausea, delirium, even coma and death [39,45].…”
Section: Resultsmentioning
confidence: 99%
“…It is defined by a serum, plasma, or blood sodium concentration below the reference laboratory range, which for most laboratories is <135 mmol/L [44]. Exercise-associated hyponatremia is serious and one of the potential causes of exercise-associated collapse [45] which can be fatal [42]. While sometimes asymptomatic, EAH can result in a myriad of signs and symptoms mimicking other conditions, including confusion, dyspnea, nausea, delirium, even coma and death [39,45].…”
Section: Resultsmentioning
confidence: 99%
“…3,7,16,17 In addition, inadequate suppression of antidiuretic hormone secretion (arginine vasopressin) affected by nonosmotic stimuli, including excessive exercise, nausea, vomiting, pain, and plasma volume contraction, could contribute to a reduction in the excretion of free water from the kidneys. 2,3,7,16,17 Similarly, studies of marathon runners and triathletes have shown a significant inverse linear association between [Na þ ] and percent change in body weight such that weight gain correlates with worsened EAH. 8,16 Several factors unique to the multistage ultramarathon may contribute to the potential development of EAH in the setting of overconsumption of fluids during a race.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Delayed diagnosis and treatment could result in serious consequences, including seizures, pulmonary edema, or death. 16,17,21 Therefore, understanding dysnatremia and hydration status in multistage ultramarathons is of the utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Ist das Körpergewicht nach dem Sport höher als zu Sportbeginn, wurde zu viel getrunken. Dieses als "Overdrinking" bezeichnete Phänomen ist die Hauptursache für eine kritische Natrium-Blutkonzentration von weniger als 135 mmol Na/Liter Blut während der Aktivität [4][5] [6]. Seit 1985 wurden weltweit 14 Todesfälle durch eine sportbedingte Hyponatriämie (EAH = Exercise-associated Hyponatremia) dokumentiert [7].…”
Section: Zu Wenig Und Zu Viel Getrunken Schränkt Leistungsfähigkeit Einunclassified